Neutrophil Migration and Adhesion Molecule Expression after Acute High-Intensity Street Dance Exercise. (8th July 2018) - Borges, Leandro; Dermargos, Alexandre; Gray, Stuart; Barros Silva, Maysa B.; Santos, Vinicius; Pithon-Curi, Tania Cristina; Gorjão, Renata; Hatanaka, Elaine
Abstract : The physical demands of street dancing may result in inflammation and changes in leukocyte numbers/function, impairing the health of dancers. Herein, we investigated the effect of street dancing on inflammation, adhesion molecules, and neutrophil function. Fifteen amateur dancers (mean ± SE: age 22.4 ± 1.08 years, BMI 24.8 ± 0.69 kg/m 2, and body fat 12.3 ± 1.52%) participated in a single high-intensity street dance class. Blood samples were taken before and after the class. The dance class had no effect on the plasma concentration of CRP, TNF- α, IL-6, IL-10, and IL-8; however, we noted an increase in levels of IL-1 β (4.06%) and sL-selectin (17.67%). The dance class resulted in a 12.36% increase in neutrophil counts, while neutrophil CD62L expression and migration were reduced (25.27% and 78.92%, resp.). After the dance class, neutrophil production of IL-8 and TNF- α increased, respectively, by 59.75% and 49.23%, in the control condition, and 43.55% and 32.22%, after LPS stimulation. A single bout of street dancing induced inflammation and reduced neutrophil migration and adhesion molecule expression. These findings may contribute to a better understanding of the susceptibility to infection after acute dance exercise.